Immunological considerations in in utero hematopoetic stem cell transplantation (IUHCT) - Loewendorf, Andrea I.; Csete, Marie; Flake, Alan (Frontiers in Pharmacology, 2015)
In utero hematopoetic Stem cell transplantation (IUHCT) is an attractive approach and a potentially curative surgery for several congenical hematopoetic diseases. In practice, this application has succeeded only in the context of Severe Combined Immunodeficiency Disorders. Here, we review potential immunological hurdles for the long-term establishment of chimerism and discuss relevant models and findings from both postnatal hematopoetic stem cell transplantation and IUHCT.